2005
DOI: 10.1097/01.brs.0000172155.17239.fa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Spinal Fusion With Recombinant Human Bone Morphogenetic Protein-2 Delivered by a Synthetic Polymer and β-Tricalcium Phosphate in a Rabbit Model

Abstract: Consistent spinal fusion was obtained by implanting a biodegradable bone-inducing implant composed of beta-TCP, PLA-DX-PEG, and rhBMP-2 within a period of 6 weeks. The rhBMP-2 doses required for the spinal fusion were significantly lower than those reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
(29 reference statements)
1
39
1
Order By: Relevance
“…3,4,[11][12][13] Namikawa et al used b-tricalcium phosphate and PLA-DX-PEG polymer gel as a carrier and successfully reduced rhBMP-2 doses to 15-30 mg to achieve solid spine fusion in the rabbit model. 14 In this study, the results showed 2.5 mg of rhBMP-2 alone using alginate sheet could not induce intertransverse bone formation. Moreover, the osteogenic potency of MSCs was enhanced …”
Section: Discussionmentioning
confidence: 66%
“…3,4,[11][12][13] Namikawa et al used b-tricalcium phosphate and PLA-DX-PEG polymer gel as a carrier and successfully reduced rhBMP-2 doses to 15-30 mg to achieve solid spine fusion in the rabbit model. 14 In this study, the results showed 2.5 mg of rhBMP-2 alone using alginate sheet could not induce intertransverse bone formation. Moreover, the osteogenic potency of MSCs was enhanced …”
Section: Discussionmentioning
confidence: 66%
“…To manufacture an osteoinductive artificial bone graft substitute, cytokines retaining osteoinductive activity (e.g., BMPs) have been combined with collagen and used to obtain spinal fusion in experimental animals or in human cases [1,4,5,17,25,26,35,36]. This experimental study was designed to achieve solid posterior interspinous lumbar fusion more effectively and less invasively than before with proper use of rhBMP-2 in combination with synthetic carrier materials.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of adding porous b-TCP powder was to increase the plasticity of the polymer for ease of handling, increase induced bone yields by volume expansion of the rhBMP-2-containing polymer implants and subsequently improve performance of the rhBMP-2. This new bone-inducing biodegradable porous b-TCP might provide effective artificial bone-graft substitutes with osteoinductive capacity and biodegradable properties [20,26]. At the same time, reducing the cost of production for rhBMP-2 is important if clinical use is to become widespread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterolateral fusion in adult rabbits [2-4, 8, 10-12, 20] is one such model that provides insight into the in vivo performance of bone graft materials. Calcium phosphate materials based on hydroxyapatite (HAp) [2-4, 8, 10-12, 20] or beta tricalcium phosphate (b-TCP) alone [13,16] have been reported with varied levels of osteoconductive response in the rabbit posterolateral fusion model. The addition of osteoinductive molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%